Priorities of corporate culture in the conditions of international transformations (Economics and region, 2024)
The essence of the concept of «corporate culture» is considered, the components of corporate culture, its main aspects are given, the key typologies of corporate cultures are presented, which are taken into account by business practitioners during its formation and evaluation of the impact on the company's development. The priorities of the company's corporate culture are reflected in the process of implementing management functions that ensure the effectiveness of the company's activities, in particular for employees, consumers (clients), state authorities and business partners. Factors that affect the level of influence of corporate culture on management processes or target groups are summarized, in particular: type of corporate culture, level of its manifestation, acceptance by employees, formalities, size of the organization. It was determined that corporate culture, like every system, has specific elements inherent only to it, in particular: values, leadership, communication, training and development, cooperation and team building, rituals and symbols, systems and processes, response to changes. These elements interact, creating a specific character of corporate culture, which determines the way of functioning and organization of interaction of its members. It is substantiated that in the conditions of international transformations, corporate culture is important for any organization, because managing it can influence the motivation of employees, the attractiveness of the enterprise as an employer; for each employee, his business reputation; on productivity and efficiency of labor activity; quality of work of employees; the nature of personal and industrial relations in the organization; creative potential of employees.
Keywords: corporate culture; corporate ethics; international transformations; globalization; leadership; business